2011
DOI: 10.1177/1545968311425927
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing 2 Interventions for Visual Field Loss With Standard Occupational Therapy During Inpatient Stroke Rehabilitation

Abstract: CT improved functional deficits after visual field loss compared with standard OT and may be the intervention of choice during inpatient rehabilitation. A larger trial that includes lesion location in the analysis is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…[848][849][850] Mödden et al 850 concluded that computer-based compensatory therapy improved functional deficits after visual field loss compared with compensation strategies training (ie, standard OT). A 2010 study 848 concluded that multimodal audiovisual exploration training is more effective than exploration training alone.…”
Section: Winstein Et Al Guidelines For Adult Stroke Rehabilitation Anmentioning
confidence: 99%
“…[848][849][850] Mödden et al 850 concluded that computer-based compensatory therapy improved functional deficits after visual field loss compared with compensation strategies training (ie, standard OT). A 2010 study 848 concluded that multimodal audiovisual exploration training is more effective than exploration training alone.…”
Section: Winstein Et Al Guidelines For Adult Stroke Rehabilitation Anmentioning
confidence: 99%
“…While it is unlikely that rehabilitation will result in recovery from a hemianopia, computer-based compensatory therapy may assist in directing visual search and attention into the area of loss [59]. The direct dopamine agonist rotigotine modestly lessened hemispatial neglect in sub-acute stroke patients [60].…”
Section: Interventions For Visual Field Deficits and Inattentionmentioning
confidence: 99%
“…Six studies (i.e., Jadad ≥3) [2,4,13,23,31,48] but one (i.e., Jadad ≤2) [26] have high quality (Table 2).…”
Section: Data Qualitymentioning
confidence: 99%